The efficacy of Staphylococcus aureus dry biomass in the detection of Cd(II) heavy metal ions - Pishva, Parsa; Bayazıt, Mustafa Kemal; Kurt, Hasan; Yüce, Meral (Springer Nature, 2022)
Environmental monitoring of heavy metal ions is vital due to their hazardous nature to living organisms. Among them, Cd(II) is a highly carcinogenic ion that interferes with the enzymatic reactions responsible for repairing the genetic replication errors. We have developed Staphylococcus aureus dry biomass–modified carbon paste electrodes to detect Cd(II) in solution as an alternative to widely used Hg-based electrodes. Due to their gram-positive thick peptidoglycan cell wall, heat-dried S. aureus biomass powder showed high binding capacity towards divalent cations. It was observed that S. aureus biomass immensely improved the detection capability of carbon paste. S. aureus–based biomass modified carbon paste electrode was optimized for better signals by investigating different buffer media and preconcentration times with cyclic voltammetry (CV) and differential pulse anodic stripping voltammetry (DPASV) techniques. The Cd(II) biosensing performance showed promising results with the detection limit reaching 44.58 nM with a dynamic range of 100 nm to 2 µM and a preconcentration time of 15 min in phosphate-buffered saline buffer pH 6. The selectivity and interference of other divalent ions showed a low level of interference with DPASV response until the concentration of 500 nM. The work underlines the efficacy of S. aureus–based biomass in cost-effective and green detection of divalent cations of heavy metals.
Keywords: Bacteria; Cd(II) Sensor; Divalent Cations; Electrochemical Sensor; Heavy Metal Sensing; Microbial Detection; Staphylococcus Aureus